2006
DOI: 10.1097/icl.0b013e31802b413f
|View full text |Cite
|
Sign up to set email alerts
|

Biocide Uptake in Contact Lenses and Loss of Fungicidal Activity During Storage of Contact Lenses

Abstract: OPTI-FREE Express and OPTI-FREE RepleniSH multipurpose disinfecting solutions maintained fungicidal efficacy after storage of lenses. The Alexidine- and PHMB-based multipurpose solutions tested showed significant uptake of preservative into group IV lenses, resulting in a decrease in the residual activity of the storage solution. The POLYQUAD systems showed a low uptake of biocide and maintained fungicidal efficacy against F. solani.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 6 publications
1
50
1
2
Order By: Relevance
“…Apresentam propriedades de limpeza, desinfecção, remoção de depósitos de proteínas e lubrificação, que simplificam as etapas dos cuidados por parte dos usuários (12)(13)(14) . Vários são os princípios ativos usados nas soluções multiuso, dos quais destacam-se o poliquaternário-1 a 0,001% (Polyquad ® ), o miristamidopropil dimetilamina a 0,0005% (Aldox ® ) e o poliaminopropil biguanida a 0,0001% (Dymed ® ) (14)(15) .…”
Section: Resumo Introduçãounclassified
“…Apresentam propriedades de limpeza, desinfecção, remoção de depósitos de proteínas e lubrificação, que simplificam as etapas dos cuidados por parte dos usuários (12)(13)(14) . Vários são os princípios ativos usados nas soluções multiuso, dos quais destacam-se o poliquaternário-1 a 0,001% (Polyquad ® ), o miristamidopropil dimetilamina a 0,0005% (Aldox ® ) e o poliaminopropil biguanida a 0,0001% (Dymed ® ) (14)(15) .…”
Section: Resumo Introduçãounclassified
“…Co-contamination of contact lens care systems with Acanthamoeba and bacteria capable of supporting amoebic growth may be the first step in the pathogenesis of Acanthamoeba keratitis by the provision of large inocula of amoebae [44]. Conversely, little is known about the role played by fungal and bacterial co-contamination of contact lens care systems in the pathogenesis of fungal keratitis.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, it is possible that co-contamination of the lens case with P. aeruginosa and F. solani may decrease the antifungal activity of ReNu with MoistureLoc. Numerous researchers have attempted to explain the epidemic; causative factors hypothesized include direct uptake of alexidine by the contact lenses (thereby reducing its antimicrobial efficacy) [44], exposure of ReNu with MoistureLoc to prolonged temperature elevation [32], reduced antimicrobial activity of evaporated ReNu with MoistureLoc [45], enhanced growth of Fusarium spp on contact lens and lens case biofilm [46], direct penetration of Fusarium spp into soft contact lenses [47], and patient non-compliance with manufacturer's recommendations (e.g.. storing the lenses without emptying and replacing the solution in the case every day, just adding extra solution to the case, etc.) [14,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of laboratories have recently reported the findings of experimental studies seeking to account for the outbreak related to use of ML (1,7,11,13,14,18,19,27,34). Imamura et al concluded that the formation of biofilms on various types of contact lenses and the consequent reduced susceptibility to lens cleaning solutions played a role in the outbreak of Fusarium keratitis (14).…”
mentioning
confidence: 99%